1975
DOI: 10.1002/aja.1001440107
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the follicular capillaries in the human spleen

Abstract: The major arteries which supply the follicular capillaries in the human spleen do not arise as they do in most mammals as lateral or radial branches from the central artery but come from penicillar arteries which penetrate the marginal zone and enter the follicle at various points around its circumference. Such arteries may have a very short course through the red pulp or they may pursue very long courses. Upon entering the follicle, these arteries branch a number of times, the branches remaining together in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The present study arteries branch off as a sheathed arteriolar-capillary bundle in a follicle, and then run independently toward the marginal zone to end as open vessels (7,20). In the present study, the follicular arteries were not elaborate in the follicle and appeared to end inside the white pulp.…”
Section: Sialoadhesin-positive Macrophages In the Human Spleenmentioning
confidence: 69%
See 2 more Smart Citations
“…The present study arteries branch off as a sheathed arteriolar-capillary bundle in a follicle, and then run independently toward the marginal zone to end as open vessels (7,20). In the present study, the follicular arteries were not elaborate in the follicle and appeared to end inside the white pulp.…”
Section: Sialoadhesin-positive Macrophages In the Human Spleenmentioning
confidence: 69%
“…For example, Snook used LM to examine periodic acid-Schiff (PAS)-stained serial sections of human spleens and reported that the central artery running adjacent to a splenic follicle did not directly give off follicular arteries but ultimately divided into penicillar arteries to supply the red pulp of the spleen (21). He further showed that some branches of the penicillar arteries, however, return and enter the splenic follicle to become follicular arteries, which in turn issue smaller branches within the follicle as an arteriolar-capillary bundle (20) and open into the marginal zone (3,20). Scanning electron microscopy (SEM) has clearly shown three-dimensionally that penicillar arteries become sheathed arteries and open into the red pulp (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From this special location of the germinal centers, one may conclude that the distribution of germinal centers in the chicken spleen is not random but rather confined to sites close to the hilus. No vascular channels were observed in the chicken's splenic germinal centers, which is in contrast with mammalian spleens (Snook, 1975).…”
Section: Discussionmentioning
confidence: 85%
“…The distribution of the splenic arterial system was outlined by staining the reticular fibers of the vessels with PAS [Snook, 1975] or, in some instances, by perfusing the arte rial system with undiluted India ink. The macrophages were located by comparing the distribution of cells giving the metalophil reaction to those containing acid phospha tase, nonspecific esterase, or which had phagocytosed colloidal carbon, adminis tered in the form of diluted India ink.…”
Section: Introductionmentioning
confidence: 99%